2002
DOI: 10.1016/s1474-51510200046-4
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Coaching of Healthy Elderly Subjects for Invasive Cardiovascular Research with Right-Sided Catheterisation

Abstract: Background and aims: Heart failure is primarily a disorder of the elderly. To investigate a non-invasive method to diagnose heart failure in the elderly, right-sided catheterisation was needed in healthy elderly subjects. We studied the feasibility of recruitment of healthy elderly subjects for this invasive investigation and aimed to identify the factors important for recruitment and for successful participation. Methods: Healthy subjects, aged ≥65 years, were invited by advertisement in a local newspaper to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Seven studies (14%) reported that, before inclusion, their participants were informed about a payment ranging from "a small honorarium" 44 to payments above $110. 48,49 One study could only provide $5 to their participants but, in the authors' opinion, their participation rate would have been higher if the payment had been better. 44 Even though in one study incentives of about $125 were paid and in another study gift certificates of $50 were offered, the authors could not confirm that the payment had a significant impact on the willingness of individuals to participate.…”
Section: Strategies To Recruit Higher Numbers Of Older Adults Into CLmentioning
confidence: 99%
“…Seven studies (14%) reported that, before inclusion, their participants were informed about a payment ranging from "a small honorarium" 44 to payments above $110. 48,49 One study could only provide $5 to their participants but, in the authors' opinion, their participation rate would have been higher if the payment had been better. 44 Even though in one study incentives of about $125 were paid and in another study gift certificates of $50 were offered, the authors could not confirm that the payment had a significant impact on the willingness of individuals to participate.…”
Section: Strategies To Recruit Higher Numbers Of Older Adults Into CLmentioning
confidence: 99%
“…Suitable volunteers were invited to the outpatient clinic to undergo a screening programme consisting of medical history, physical examination, electrocardiography, blood laboratory analysis, bedside spirometry, bicycle stress‐electrocardiography and echocardiography. The recruitment of the subjects was described in a previous report (Bos et al. , 2002).…”
Section: Methodsmentioning
confidence: 99%
“…, 1992). In extension to these reports, we investigated the relationship of PCWP and the BP response to the Valsalva manoeuvre in healthy elderly subjects (Bos et al. , 2002), in order to get insight into the physiological BP response to the Valsalva manoeuvre and to obtain normal values.…”
Section: Introductionmentioning
confidence: 99%